Analisis Penyusunan Rencana Strategis RSUD dr. M. Yunus Bengkulu Tahun 2021-2026 - Zahrotul Lina Andarwati; Dumilah Ayuningtyas (Jurnal Ners, 2023)
The focus of this manuscript is on developing a strategic plan for a hospital, with a case study of RSUD dr. M. Yunus Bengkulu, which is a government-owned Class B Education Hospital. This research is qualitative in nature with a descriptive design. The research findings indicate that both external and internal environmental factors position RSUD dr. M. Yunus Bengkulu in the "Growth and Build" quadrant on the IE Matrix and in the "Internal Fix-It" quadrant on the TOWS Matrix. The selected alternative strategy is Market Penetration, accompanied by improvements in the hospital's weaknesses to seize existing opportunities. An Implementation Plan is devised to align with the hospital's vision of becoming a Class A Hospital with quality, progressive, competitive services, and a focus on Education and Research. In order to achieve this vision, RSUD dr. M. Yunus Bengkulu needs to identify potential market areas for expansion and address its internal weaknesses. Strategic steps must be taken to enhance service quality, increase competitiveness, and bolster research and educational capabilities within the hospital. With the right strategic planning, RSUD dr. M. Yunus Bengkulu can effectively confront changing environmental challenges, maximize growth potential, and achieve its vision of becoming an outstanding hospital with quality services and competitiveness.